Patient-Reported Symptom Burden and Supportive Care Needs of Patients With Stage II-III Colorectal Cancer During and After Adjuvant Systemic Treatment: A Real-World Evidence Study. Issue 3 (6th March 2023) - Cuthbert, Colleen A.; O'Sullivan, Dylan E.; Boyne, Devon J.; Brenner, Darren R.; Cheung, Winson Y.
Abstract : PURPOSE: Patients with colorectal cancer (CRC) experience a range of physical and psychologic symptoms, and supportive care needs throughout the illness trajectory. We used patient-reported outcomes and administrative health data to describe symptom burden and supportive care needs during and after adjuvant treatment and determine factors associated with changes to symptom burden. METHODS: A retrospective population-based cohort study of patients who were newly diagnosed with stage II-III CRC in Alberta, Canada, between January 1, 2016, and January 31, 2019. Adults age 18 years or older who completed a patient-reported outcomes survey (Edmonton Symptom Assessment System) and supportive care needs (Canadian Problem Checklist) within 3 months after starting adjuvant treatment (during treatment) and > 7 months after starting treatment (after treatment) were included. Changes to symptom severity were stratified as stable, improved, or deteriorated. Multivariable logistic regression was used to evaluate factors associated with these changes. RESULTS: We included 303 patients (median age 60 years, 62% male, 84.5% stage III, 51.2% rectal v colon). Prevalent symptoms included tiredness (80.5%), pain (50.8%), and poor well-being (50%) during treatment, and tiredness (71.3%), pain (44.2%), and poor well-being (62.1%) after treatment. The results were heterogeneous with respect to improvements, stability, or deterioration. Pain worsened for 25% of the cohort, tiredness for 28%, and depression, anxiety, and well-being for 21%, 22%, and 31%, respectively. Deterioration of some symptoms was associated with older age, stage II, comorbidities, rural setting, and higher income. CONCLUSION: We demonstrated symptom severity was generally low and most symptoms remained stable or improved after treatment. Particular groups of patients were at greater risk for more severe and/or more persistent symptoms. Ongoing assessments and interventions to address physical and psychologic symptoms, and supportive care needs in patients with CRC during and after treatment are needed.